The importance of neurophysiological-Bobath method in multiple sclerosis - Adrian Miler; Marta Podhorecka; Klara Nicpoń-Nożewska; Walery Zukow (Kazimierz Wielki University, 2018)
Rehabilitation treatment in multiple sclerosis should be carried out continuously, can take place in the hospital, ambulatory as well as environmental conditions. In the traditional approach, it focuses on reducing the symptoms of the disease, such as paresis, spasticity, ataxia, pain, sensory disturbances, speech disorders, blurred vision, fatigue, neurogenic bladder dysfunction, and cognitive impairment. In kinesiotherapy in people with paresis, the most common methods are the (Bobathian) method.Improvement can be achieved by developing the ability to maintain a correct posture in various positions (so-called postural alignment), patterns based on corrective and equivalent responses. During the therapy, various techniques are used to inhibit pathological motor patterns and stimulate the reaction. The creators of the method believe that each movement pattern has its own postural system, from which it can be initiated, carried out and effectively controlled. Correct movement can not take place in the wrong position of the body. The physiotherapist discusses with the patient how to perform individual movement patterns, which protects him against spontaneous pathological compensation.The aim of the work is to determine the meaning and application of the  Bobath method in the therapy of people with MS